Association between tobacco use, pain expression, and coping strategies among patients with advanced cancer. Issue 1 (23rd October 2018) - Dev, Rony; Kim, Yu Jung; Reddy, Akhila; Hui, David; Tanco, Kimberson; Liu, Diane; Park, Minjeong; Williams, Janet; Carmack, Cindy; Bruera, Eduardo
Abstract : Background: The objective of the current study was to evaluate the association between tobacco use, symptom expression, and coping strategies in patients with advanced cancer. Methods: The authors prospectively enrolled patients with advanced cancer and collected data regarding patient demographics, cancer diagnosis, morphine equivalent daily dose, cigarette smoking status using the Behavioral Risk Factor Surveillance System, symptom expression as measured by the Edmonton Symptom Assessment System, the Cut down/Annoyed/Guilty/Eye opener alcoholism questionnaire, the Screener and Opioid Assessment for Patients with Pain–short form survey, and the Brief COPE Questionnaire. Results: Among 399 patients, 195 (49%) were never‐smokers, 158 (40%) were former smokers, and 46 (11%) were current smokers. The most common malignancies were gastrointestinal (21%) and breast (19%). Current smokers demonstrated significantly higher pain scores at the time of consultation compared with former or never‐smokers (mean 6.4 vs 5.9 vs 5.1, respectively; P  = .015), demonstrated increased morphine equivalent daily dose (median 90 mg/day vs 60 mg/day vs 50 mg/day, respectively; P  = .002), were more likely to screen as positive on the Cut down/Annoyed/Guilty/Eye opener questionnaire (33% vs 24% vs 8.7%, respectively; P  < .0001) and were more likely to screen as positive (≥4) on the Screener and Opioid Assessment for Patients with Pain–short form survey (74% vs 13% vs 9.3%, respectively; P  < .0001). Compared with former and never‐smokers, current smokers were significantly more likely to cope maladaptively with substance use ( P  = .02), denial ( P  = .007), and self‐blame ( P  < .0001). Conclusions: Among patients with advanced cancer, current and former smokers appear to be significantly more likely to have higher pain expression and thus require higher opioid doses, and to have more risk factors for using opioids in a nonprescribed manner. The results of the current study highlight the need to provide closer monitoring and increased psychosocial support for patients with cancer who smoke while receiving chronic opioid therapy. Abstract : Among patients with advanced cancer, current and former smokers appear to be significantly more likely to have higher pain expression and thus to require higher opioid doses, and to have more risk factors for the nonmedical use of opioids. The results of the current study highlight the need to provide closer monitoring and increased psychosocial support for patients with cancer who smoke while receiving chronic opioid therapy.